Online Induction Programmes: Developing and evaluating transitional online support - Goldsmith, Gerry; Millington, Clare (Proceedings of the International Conference on Networked Learning, 2002)
This workshop will explore online student induction. We will evaluate a number of examples of induction and transition programmes designed for students joining higher education. The workshop will include hands-on evaluation of a number of examples of online induction programmes. One of these will be an induction programme currently being developed for part-time postgraduate students in the School of Computing and Management Sciences at Sheffield Hallam University